Household Savings in Central Eastern and Southeastern Europe : How Do Poorer Households Save? - Beckmann, Elisabeth (World Bank, Washington, DC, 2019)
Based on a survey of households in 10 Central Eastern European and Western Balkan countries, this paper presents new and unique evidence on which households have savings and how they save. The paper shows that the percentage of savers is low, and savings are frequently informal. Formal savings are dominated by bank savings, and participation in contractual and capital market savings is very low in comparison to high-income countries. Poor households are significantly less likely to have any savings; income also has an effect, albeit smaller, on the choice of formal versus informal savings. With a high density of bank branches in Central Eastern European and Western Balkan countries lack of physical access to banks does not explain the lack of formal savings. Lack of trust in banks reduces the probability of formal savings, especially bank savings.